Segmentation of coastal marine demand from a National Recreational Area: Villamil Beach, Ecuador - Carvache-Franco, Mauricio; Carvache-Franco, Orly; Carvache-Franco, Wilmer; Orden-Mejía, Miguel; Macas-López, Cristina (Geographica Pannonica, 2018)
Tourist demand segmentation can provide important information for creating products tailored to the clusters found. The present empirical work was carried out in situ in Ecuador at the Villamil Beach National Recreation Area, a coastal marine destination within a national recreation area. Factor analysis on responses by tourists to a questionnaire produces two motivational dimensions: "Ecotourism" and "Sun and beach". Three tourist segments are found: “Beach lovers”, who have high motivations for enjoying the sun and the beach, "Coastal Nature", who have high motivations for enjoying the typical gastronomy, for the sun and the beach, for the tourist attractions and for knowing the flora and fauna and, finally, "Coastal Passive", who have medium and low motivations in all aspects.